PENGEMBANGAN INSTRUMEN PENILAIAN KETERAMPILAN PROSES SAINS PADA PEMBELAJARAN FISIKA SMA - Nazwatul Ilmi; Desnita Desnita; Erfan Handoko; Betty Zelda (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
The curriculum 2013 emphasizes learning physics using process skills approach to develop the scientific skills of students. Based on need analysis obtained that the assessment instruments used by teachers is not in accordance with the process of learning. The aims of this research is to produce a science process skills assessment instruments in learning physics for high school students. The instrument was developed restricted to direct current circuit subject. The method used in this research is the development of research. The instrument was developed thirty- five test items written in the form of multiple choice. Science process skills indicatorsinclude observing, formulating a hypothesis, identifying variables, interpreting data, communicating, and implementing concept. Expert validation is done by using observation sheet with Likert scale. Keywords: Instrumen, assessment, science process skill.